HAZAIRIN DAN PENGHAPUSAN PIDANA PENJARA PENDEK - Ninik Zakiyah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2016)
This writing describes Hazarin thought of the ineffectiveness of short imprisonment in Indonesia and the study of possibility replacement of short prison sentences with social penalties. Hazarin said that short imprisonment is ineffective to give deterrent effect, and may even lead to negative stigmas and consequences such as the prisoners will become more virulent after being released from prison, that make people reject the presence of ex-prisoners. Hazarin offers the concept of criminal work in the public interest without being paid in lieu of imprisonment. He also offers customary or Islamic law penalty to replace the short imprisonment as an alternative. Thus the replacement of the short sentence of imprisonment is in accordance with Islamic law and the first principle of Pancasila, the divinity of the God, the Almighty, who gives the human soul religious consciousness. Besides that, it is also in accordance with the fifth principle of Pancasila, the development of human awareness through moral education and justice for peace and justice social life. However, with the current conditions in Indonesia, the Hazainin thought doesn’t seem applicable.